(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The sales volume function has a crucial role in ensuring the longevity of a business or a product in the market. In this case, sales volume is the number of units sold of a product specified in a certain period. If the sales in a company can be increased then the profits in that company will also increase. A good distribution channel will influence customer interest. Distribution channels are a company’s decision to place the products it produces at the right time and place. This research consisted of 50 respondents. Sample selection involved utilizing the entire population, while data analysis employed multiple regression analysis. Data processing was conducted using the SPSS Windows program. The outcomes of the study indicate a positive yet insignificant relation between distribution channels and sales, a beneficial and noteworthy influence of product innovation on sales, and a positive correlation between distribution channels, product innovation, and sales.